Carbon criminals, climate crimes - Kramer, Ronald C. (New Brunswick, New Jersey : Rutgers University Press, 2020)
"Carbon Criminals, Climate Crimes analyzes the looming threats posed by climate change from a criminological perspective. It advances the field of green criminology through a examination of the criminal nature of catastrophic environmental harms resulting from the release of greenhouse gases. The book describes and explains what corporations in the fossil fuel industry, the US government, and the international political community did, or failed to do, in relation to global warming. Carbon Criminals, Climate Crimes integrates research and theory from a wide variety of disciplines, to analyze four specific state-corporate climate crimes: continued extraction of fossil fuels and rising carbon emissions; political omission (failure) related to the mitigation of these emissions; socially organized climate change denial; and climate crimes of empire, which include militaristic forms of adaptation to climate disruption. The final chapter reviews policies that could mitigate greenhouse gas emissions, adapt to a warming world, and achieve climate justice"--
"This was a crime:" climate change as a criminological concern -- "Beyond catastrophic:" the climate crisis, carbon criminals, and fossil capitalism -- "When did they know"? Climate crimes of continued extraction and rising emissions -- "The politics of predatory delay:" climate crimes of political omission and socially organized denial -- "Slowing the rise of the oceans"? Obama's mixed legacy and Trump's climate crimes -- "Blood for oil," Pentagon emissions, and the "politics of the armed lifeboat:" climate crimes of empire -- The "climate swerve:" hope, resistance, and climate justice.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on December 30, 2024).
eBooks on EBSCOhost
Keywords: Offenses against the environment; Criminology -- Environmental aspects; Climatic changes -- Moral and ethical aspects; Global warming -- Moral and ethical aspects; Climatic changes -- Government policy; Global warming -- Government policy; Corporations -- Corrupt practices; Environmental justice; Crimes contre l'environnement.; Criminologie -- Aspect de l'environnement.; Climat -- Changements -- Aspect moral; Réchauffement de la Terre -- Aspect moral; Réchauffement de la Terre -- Politique gouvernementale; Sociétés -- Pratiques déloyales.; Justice environnementale; SCIENCE -- General; Climatic changes -- Government policy; Climatic changes -- Moral and ethical aspects; Corporations -- Corrupt practices; Environmental justice; Global warming -- Government policy; Global warming -- Moral and ethical aspects; Offenses against the environment; Carbon Criminals, Climate Crimes, criminological perspective, carbon emissions, political omission, mitigation, Criminological Concern, Climate Crisis, Fossil Capitalism, Pentagon Emissions, Hope, Resistance, Climate Justice, Criminal Justice, Law, Current Affairs, Sociology, Public Policy, Environment, Ecology, Social science, Criminology, Political Science, Corruption, Misconduct, Global Warming, Climate Change, Science, environmental science, Environmental Policy; Electronic books